ANAK DISABILITAS DALAM KARYA LUKIS KONTEMPORER - IKHBAL PENDAWA, Drs. Abd. Hafiz, M.Pd., Drs. Efrizal, M.Pd. (Universitas Negeri Padang, 2019)
The final work aims to create a contemporary realistic art painting with children’s objects of disability. The method of creation works using five steps, i.e, preparation, elaboration, synthesis, concept realization, and completion. The objects displayed in the form of life and daily lives of children with disabilities then the treatment of society given to them based on the actual events that have occurred, with the title of the work: (1)